Polimarlish.id, a game-based learning website to meet the standard marine communication phrases proficiency - Sari, Dhesi Wulan; Herdawan, Deri; Kurniawan, Fajar Sari; Marselia, Marselia; Anggoro, Retno (Journal of Education and Learning (EduLearn), 2025)
Previous studies suggested that game learning method could assist students in improving English proficiency. However, Gen Z students in a semi-military maritime vocational school had a lack of motivation to enrich their maritime English mastery because of their many non-academic activities. The goal of this study was to present polimarlish.id as an alternative game learning medium to enhance maritime English phrases, vocabulary, and idioms through interactive game-learning such as matching pictures, matching sounds, jumbled words, and fill-in-the-blank. This website was developed by considering various types of games and details of the user experience, such as giving clear instructions, attaching real pictures, and using a native sound speaker. Therefore, in order to evolve this game-based learning website, the researcher also gained data by taking observations, conducting interviews, and delivering questionnaires. The data was analyzed using a Likert scale. A total of 85.71% of 28 participants agreed that polimarlish.id could enhance their maritime English standard marine communication phrases (SMCP) proficiency.